Kode Etik Jaksa Berdasarkan Undang-Undang Dasar 1945 - Putri, Yunisha Dena; Budiyono, Budiyono; Muhtadi, Muhtadi (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This study stems from the growing need to uphold ethical standards within the Indonesian judicial system, particularly concerning prosecutors, who play a pivotal role in law enforcement and justice. The lack of a specific and binding code of ethics for prosecutors has raised concerns about accountability, professionalism, and integrity in the exercise of their duties. This research aims to analyze the urgency of establishing a code of ethics for prosecutors and examine the standards of ethical behavior in accordance with the 1945 Constitution of the Republic of Indonesia. This is a normative legal study employing a legislative and conceptual approach. Data were collected through an extensive literature review and analyzed using qualitative methods. The findings indicate that a dedicated code of ethics is essential for guiding prosecutors in carrying out their duties, functions, and authorities with integrity, professionalism, and wisdom. Ethical integrity emphasizes loyalty to Pancasila and the 1945 Constitution, while professionalism demands adherence to legal and institutional regulations. Wisdom reflects the prosecutor’s responsibility as a public servant who respects prevailing religious, moral, and societal norms. Ethical standards are an extension of the rule of law principle as enshrined in Article 1 paragraph (3) of the 1945 Constitution.